Genome-wide association study identifies five new schizophrenia loci - Ripke, Stephan; Sanders, Alan R; Kendler, Kenneth S; Levinson, Douglas F; Sklar, Pamela; Holmans, Peter A; Lin, Dan-Yu; Duan, Jubao; Ophoff, Roel A; Andreassen, Ole A; Scolnick, Edward; Cichon, Sven; et al. (Nature genetics, 2011)
The Schizophrenia Psychiatric Genome-Wide Association Study Consortium reports five genetic loci newly associated with risk of schizophrenia, involving 17,836 cases of schizophrenia and 33,859 healthy controls. The new locus with the strongest support of association was located within an intron for microRNA 137, a known regulator of neuronal development. Four other genome-wide significant loci for schizophrenia contain predicted targets of MIR137 , suggesting that disruption to pathways involving MIR137 may be an etiologic mechanism in schizophrenia. We examined the role of common genetic variation in schizophrenia in a genome-wide association study of substantial size: a stage 1 discovery sample of 21,856 individuals of European ancestry and a stage 2 replication sample of 29,839 independent subjects. The combined stage 1 and 2 analysis yielded genome-wide significant associations with schizophrenia for seven loci, five of which are new (1p21.3, 2q32.3, 8p23.2, 8q21.3 and 10q24.32-q24.33) and two of which have been previously implicated (6p21.32-p22.1 and 18q21.2). The strongest new finding ( P = 1.6 × 10 −11 ) was with rs1625579 within an intron of a putative primary transcript for MIR137 (microRNA 137), a known regulator of neuronal development. Four other schizophrenia loci achieving genome-wide significance contain predicted targets of MIR137 , suggesting MIR137 -mediated dysregulation as a previously unknown etiologic mechanism in schizophrenia. In a joint analysis with a bipolar disorder sample (16,374 affected individuals and 14,044 controls), three loci reached genome-wide significance: CACNA1C (rs4765905, P = 7.0 × 10 −9 ), ANK3 (rs10994359, P = 2.5 × 10 −8 ) and the ITIH3-ITIH4 region (rs2239547, P = 7.8 × 10 −9 ).